Multiple positive solutions of singular fractional differential system involving Stieltjes integral conditions - Jiang, J.; Liu, L.; Wu, Yong Hong (University of Szeged, 2012)
In this paper, the existence and multiplicity of positive solutions to singular fractional differential system is investigated. Sufficient conditions which guarantee the existence of positive solutions are obtained, by using a well known fixed point theorem. An example is added to illustrate the results.